1977
DOI: 10.1111/j.1432-0436.1977.tb01506.x
|View full text |Cite
|
Sign up to set email alerts
|

Frequencies of Circular Units of Nucleolar DNA in Oocytes of Two Insects, Acheta domesticus and Dytiscus marginalis, and Changes of Nucleolar Morphology during Oogenesis

Abstract: The organization of the extrachromosomal nucleolar material in oocytes of two insect species with different ovary types, the house cricket Acheta domesticus (panoistic ovary) and the water beetle Dytiscus marginalis (meroistic ovary), was studied with light and electron microscopic techniques. Stages early in oogenesis were compared with fully vitellogenic stages (mid-to-Iate diplotene). The arrangement of the nucleolar material undergoes a marked change from a densely aggregated to a dispersed state. The latt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

1977
1977
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 67 publications
0
15
0
Order By: Relevance
“…Such intra-axial heterogeneity is hardly explained by an amplification mechanism which involves starting units which contain only one pre-rRNA gene (for discussion see Wellauer et aL, 1976 b) , The existence of different rDNA units in the same amplified molecule seems to be compatible with the widely accepted concept that amplification takes place via a "rolling circle" mechanism (Hourcade et aL, 1973 ;Rochaix et aL , 1974 ;Bakken, 1975;Buongiorno-Nardelli et aL, 1976) only if one allows for multigenic rDNA circIes containing different units in the initial steps of the replicative process. Adjacent repeating units of different sizes have recently also been described in the amplified rDNA of the oocytes of two insect species, Dytiscus marginalis and Acheta domesticus (Trendelenburg et aL, 1976(Trendelenburg et aL, , 1977. Moreover, size differences of rDNA repeating units in the same strand (intraaxial heterogeneities) have been noted in spread prepanÜions of nucIeoli from primary nucIei of dasycladacean green algae (Spring et aL, , 1976Trendelenburg et aL, 1974) and from embryonic cells of Drosophila melanogaster (e.g.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Such intra-axial heterogeneity is hardly explained by an amplification mechanism which involves starting units which contain only one pre-rRNA gene (for discussion see Wellauer et aL, 1976 b) , The existence of different rDNA units in the same amplified molecule seems to be compatible with the widely accepted concept that amplification takes place via a "rolling circle" mechanism (Hourcade et aL, 1973 ;Rochaix et aL , 1974 ;Bakken, 1975;Buongiorno-Nardelli et aL, 1976) only if one allows for multigenic rDNA circIes containing different units in the initial steps of the replicative process. Adjacent repeating units of different sizes have recently also been described in the amplified rDNA of the oocytes of two insect species, Dytiscus marginalis and Acheta domesticus (Trendelenburg et aL, 1976(Trendelenburg et aL, , 1977. Moreover, size differences of rDNA repeating units in the same strand (intraaxial heterogeneities) have been noted in spread prepanÜions of nucIeoli from primary nucIei of dasycladacean green algae (Spring et aL, , 1976Trendelenburg et aL, 1974) and from embryonic cells of Drosophila melanogaster (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Under preparative conditions that perfectly allow the deposition of single gene units of rDNA on the specimen grid (cf. Trendelenburg et al, 1976Trendelenburg et al, , 1977 we found only very rarely short linear or circular units (only three rings containing five and six repeating units, respectively, were encountered among a total of seve ral thousand repeating units evaluated, cf. Miller and Beatty, 1969 ; in general, rings of nucleolar chromatin were much rarer in oocytes of Xenopus laevis than in those of Triturus alpestris and T. cristatus).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Electron micrograph of a positively stained spread preparation of a ring of nucleolar chromatin isolated from diplotene oocytes of the water beetle, Dytiscus marginalis (for preparative details see Trendelenburg et al 1976Trendelenburg et al , 1977. This ring contains two transcribed genes coding for precursors to ribosomal RNAs and the interspersed apparent spacer intercepts.…”
Section: Description Of Platementioning
confidence: 99%